Processualità e ideologia ne L'ideologia tedesca = Process and ideology in The German Ideology. - Gabriele Schimmenti (H-ermes: Journal of Communication, 2016)
The aim of my paper is to discuss the subject of ideology with some passages of I. Feuerbach of Marx and Engels's German Ideology manuscripts, pointing out how its processual feature is indispensable to understand some utterances as well as some changes of the manuscripts. Before I start with c) my theorethical considerations and in order to obtain the above-mentioned results, I will make the point of a) some philological issues about the recent discoveries that concerns German Ideology and b) some aspects of the “political history” of editions. The philological account allows us to consider the issue of criticism of ideology in its own dimension. It is worth noting that the German Ideology can not be conceived as a work and that it is constituted by re-elaborated versions of journalistic writings